PENDEKATAN SAINTIFIK DENGAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER DAPAT MENINGKATKAN HASIL BELAJAR ROLL BELAKANG - Hasniah Hasniah; M Irfan Hasanuddin (STKIP Paris Barantai, 2022)
This research that aims to discover the level of learning outcomes through a scientific approach with the Number Head Together learning model in grade IV students at SDN 5 Baharu Selatan Kotabaru. The study was conducted in two cycles where each cycle consisted of four stages, namely: planning, acting, observing, and reflecting. Data collection of learning outcomes was conducted by using Observation Sheets, Worksheets, and the backroll ability test at the end of the cycle. The collected data were then analyzed by Benchmark Reference Approach and quantitatively. Based on those data, the result of the backroll technique shows that students who completed the learning in the first cycle were 6 people with a percentage of 30%, and students who did not complete the learning were 14 people with a percentage of 70%. In cycle II, 17 students completed the learning with a percentage of 85% and 3 students who did not complete the learning with a percentage of 15%. Based on the results of the study it can be concluded that the implementation of a scientific approach with the Number Head Together learning model can improve the learning outcomes. Key words: Scientific Approach, Number Head Together, the result of study.